Detection of nineteen enteric viruses in raw sewage in Japan - Thongprachum, Aksara; Fujimoto, Tsuguto; Takanashi, Sayaka; Saito, Hiroyuki; Okitsu, Shoko; Shimizu, Hiroyuki; Khamrin, Pattara; Maneekarn, Niwat; Hayakawa, Satoshi; Ushijima, Hiroshi (Infection, genetics and evolution, 2018)
One-year surveillance for enteric viruses in raw sewage was conducted in Kansai area, central part of Japan from July 2015 to June 2016. The raw sewage was collected monthly from an inlet polluted pool and was concentrated by polyethylene glycol (PEG) precipitation. Twelve sewage samples were screened for nineteen kinds of enteric viruses by using RT-PCR method and further analyzed by nucleotide sequencing. Twelve enteric viruses were found in the investigative sewage samples. Rotavirus A and norovirus GI and GII with several genotypes were detected all year round. Interestingly, norovirus GII.17 (Kawasaki-like strain) and rotavirus G2 that caused the outbreaks in Japan last epidemic season were also found in sewage. Moreover, adenovirus, astrovirus, sapovirus, bocavirus, human parechovirus, enterovirus, Aichi virus, Saffold virus and salivirus were also detected. Enterovirus D68 was detected only in the same month as those of enterovirus D68 outbreak in Japan. The rotavirus B and C, hepatitis A and E viruses, human cosavirus, bufavirus and rosavirus were not detected in this surveillance. The study provides the information on the enteric viruses contaminated in raw sewage, which is valuable for risk assessment. Our results imply that the viruses detected in sewage may be associated with infections in the Japanese population. •This study provides the one-year surveillance of 19 enteric viruses in sewage in Japan.•A wide variety of diarrheal viruses were found in all Japanese sewage samples.•Rotavirus A and norovirus GI and GII with several genotypes were detected all year round.•Norovirus GII.17 and rotavirus G2 caused the outbreaks in Japan were found in sewage.•The enteric viruses detected in sewage may associate with infections in Japanese population.